Novel cascaded control systems for microfluidic devices - Li, Yuezhao (2020)
In the past decades, the scientific community is committed to understanding the mechanism of information encoding in the brain. Establishing a controlled micro-scale physiochemical environment in vitro is able to simulate the neuronal network in the brain and thus becomes a popular research topic. In order to keep cells or neurons to live homeostatically in the cell culture, it is necessary to supply nutrients and remove wastes continuously. The observation of cell activities in the cultured network has high spatial and temporal requirements. The speed of the drug delivery should be controlled precisely in order to prevent the generation of large shear stresses and air bubbles. In addition, the response of the drug delivery system should be fast enough to capture the signals processing among the target cells. Development of microfluidic techniques has improved the quality of cell cultivation performed in the micro-scale environment. Emergence of advanced liquid handling techniques such as droplet mixers and syringe pump injections has achieved efficient reagent and drug delivery while minimising wastes. However, the requirements for the microfluidic control techniques vary with applications and these liquid handling techniques are limited by their characteristics including complex structure, specific application range and high manufacture cost. Therefore, a simple and accurate microfluidic control system with high scalability and reasonable price is in high demand. In this research project, a novel cascaded microfluidic control system has been developed to accurately control the flow rate of the cell culture media delivery to establish a simulated physiochemical environment for neurons to live homeostatically for a certain amount of time. With the aid of modern control algorithms and advanced microcontrollers, the cascaded microfluidic control system is able to reach the target flow range of 0 to 60nl⁄s within seconds. Compared with mature commercial microfluidic control systems such as the ELVEFLOW OB1 MK3 system, the precision of the cascaded microfluidic control system has also reached the level of nl⁄s. The whole structure of the cascaded microfluidic control system is simple and all the components of the hardware can be easily replaced. Following the research trend of Miniaturised Total Analytical Systems (µ-TAS systems), the total volume of the hardware has been improved to a portable size around 5L to replace the conventional bulky systems. Moreover, an advanced open source software environment has been developed with the aid of open source platform NetBeans and object-oriented programming language JAVA to realize the functions of variables graphical display, control parameters setting, and control commands execution. The software development enables the microfluidic control system to be used for a long period with minimal supervision. In addition, compared with other microfluidic control applications, the manufacture cost has been saved up to three times. All these features have enabled the novel cascaded microfluidic control system of high scalability and thus it can be used in different cell culture applications with minimal changes. Therefore, in addition to achieving rapid cell culture media delivery, the novel cascaded microfluidic control system can also be integrated with other applications to develop an advanced real-time cell culture monitoring system in the future. Through electrical stimulation, chemical rewarding and high-level optical recording techniques, the advanced system is able to monitor the whole process of cell activities, which will make great contributions to the cellular biology research.